Does the median preoptic nucleus contribute to sympathetic hyperactivity in spontaneously hypertensive rats? - Mourao, Aline A.; Moreira, Marina C. S.; Melo, Aryanne B. S.; Lopes, Paulo R.; Rebelo, Ana C. S.; Rosa, Daniel A.; Freiria-Oliveira, Andre H.; Colombari, Eduardo [UNESP]; Pedrino, Gustavo R. (Elsevier B.V., 2016)
The present study sought to determine the involvement of median preoptic nucleus (MnPO) in the regulation of the cardiovascular function and renal sympathetic activity in normotensive (NT) and spontaneously hypertensive rats (SHR). MnPO inhibition evoked by Muscimol (4 mM) nanoinjections, elicited fall in MAP and renal sympathoinhibition in NT-rats. Surprisingly, in SHRs these responses were greater than in NT-rats. These results demonstrated, for the first time that MnPO was involved in the tonic control of sympathetic activity in NT and SHRs. Furthermore, our data suggest the MnPO involvement in the increased sympathetic outflow and consequent arterial hypertension observed in SHRs. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Arterial pressure; Hypertension; MnPO; Renal sympathetic nerve activity; SHR